Surgical management of aortic regurgitation secondary to Behcet's disease - Hu, Hai-Ou; Zhang, Chen-Han; Spadaccio, Cristiano; Tang, Bing; Li, Cheng-Nan; Qiao, Zhi-Yu; Zheng, Tie; Zhu, Jun-Ming; Sun, Li-Zhong (Frontiers in Cardiovascular Medicine, 2023)
Background Aortic regurgitation (AR) related to Behcet's disease (BD) is rare, but usually fatal. Perivalvular leakage (PVL) is high if AR related to BD treated with regular AVR. In this study, we report the surgical management of AR secondary to BD. Methods Between September 2017 and April 2022, 38 patients with AR secondary to Behcet's disease had surgery in our center. 17 patients did not have a BD diagnosis before surgery, 2 of them were diagnosed during surgery and received Bentall procedure. The remaining 15 patients received conventional AVR. 21 patients were diagnosed as BD before surgery, all of them received modified Bentall procedures. All patients were followed up by regular outpatient visits, transthoracic echocardiogram and CT angiography were performed to evaluate the aorta and aortic valve. Results Seventeen patients did not have a BD diagnosis at the time of surgery. Out of them, 15 patients received conventional AVR, and a total of 13 patients suffered PVL after surgery. Twenty-one patients had a BD diagnosis before surgery. They received modified Bentall procedures and IST and steroids were given both pre- and post-surgery. In this group treated with Bentall procedure no patient suffered PVL during follow up. Conclusions PVL is a complex scenario after conventional AVR for AR in BD. Modified Bentall procedure seems superior to isolated AVR in these cases. The use of IST and steroids before and after surgery in combination with modified Bentall procedure could have a role in effectively reducing PVL.